Analisis Limbah Cair Domestik Kantin: Strategi Inovatif untuk Pengelolaan Lingkungan yang Berkelanjutan di Universitas Panca Bhakti - Rahsia, Shandra Andina; Anggraini, Ika Muthya; Marbun, Julianti (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
The canteen at Universitas Panca Bhakti generates domestic wastewater from daily activities such as cooking, washing, and kitchen cleaning, which poses a potential threat to the environment. This study aims to identify the characteristics of the canteen's wastewater based on key pollutant parameters and to design a small-scale domestic wastewater treatment system in accordance with the quality standards set by the Ministry of Environment and Forestry Regulation No. 68 of 2016. The methodology includes wastewater sampling at three different operational times (morning, noon, and afternoon), followed by laboratory analysis of BODâ‚…, COD, TSS, oil and grease, pH, ammonia, and total coliform. The results show that all parameters exceeded the quality standard limits, with peak pollutant concentrations recorded at 3:00 PM"”BODâ‚… at 11,069 mg/L, COD at 32,373 mg/L, TSS at 28,000 mg/L, oil and grease at 2,506 mg/L, ammonia at 3.924 mg/L, and total coliform at 22,000 CFU/100 mL. Based on these findings, an integrated wastewater treatment system (IPAL) was designed, consisting of a grease trap for oil and grease removal, a sedimentation tank for suspended solids, an aerobic biofilter for organic degradation, and a disinfection unit to reduce pathogenic microorganisms. This system is expected to reduce pollutant loads to meet quality standards before the effluent is discharged into the environment.